Gamification as an innovative instrument in business management - Забуга, Сергей Иванович; Гадецкий, Вадим (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The article describes main mechanisms of gamification, its field of application, andexamples of its use in the enterprise, social networks and mobile computing applications. Gives an algorithm of creating the game, modeling the number of players depending on the time using the Gompertz function.